Gambaran Harga Diri Pada Siswa Sekolah Menengah Tingkat Atas - Fransiska Salamun; Widyo Subagyo; Dyah Wahyuningsih (Prodi Keperawatan Purwokerto, 2021)
Background: Self-esteem can threaten a person's development during puberty, self-esteem that changes at this time affects him in decisions, position choices and determines his participation in activities. teenager As a person who is developing from a child to an adult but has not been able to take full responsibility. This requires parental assistance both at home and at school in every teenager making important decisions.Methods: This research method uses descriptive analytic design with a cross sectional approach. the research population is high school students as many as 463 students. The sample was selected and obtained 101 students who participated in this study. The results of the questionnaire assessment were analyzed using computerized media.The results: the results showed that more than half of the respondents had high self-esteem, namely 55%. some have low self-esteem or are having problems. This can occur due to various factors including the development of unsuccessful transitions during adolescence, having problems in the family, having personal problems both physically and psychologically.Conclusion: observing the results of research like this, the number of students who have low self-esteem needs to be taken anticipatory steps from the parents and after. Families must always provide support for teenagers. schools must provide psychological services and counseling facilities for students. Many methods are used to foster adolescent self-esteem, namely improving the quality of relationships in schools, study groups, differences in interests and talents in extra-curricular activities, holding positive activity contests such as subject competitions and others.